Radiation Dose and Fluoroscopy Time of Endovascular Coil Embolization in Patients with Carotid Cavernous Fistulas - Yigit Ozpeynirci; Christoph Gregor Trumm; Robert Stahl; Thomas Liebig; Robert Forbrig (Diagnostics, 2022)
Carotid cavernous fistulas (CCFs) are abnormal connections between the cavernous sinus and the internal and/or external carotid artery. Endovascular therapy is the gold standard treatment. In the current retrospective single-center study we report detailed dosimetrics of all patients with CCFs treated by endovascular coil embolization between January 2012 and August 2021. Procedural and dosimetric data were compared between direct and indirect fistulas according to Barrow et al., and different DSA protocol groups. The local diagnostic reference level (DRL) was defined as the 3rd quartile of the dose distribution. In total, thirty patients met the study criteria. The local DRL was 376.2 Gy cm2. The procedural dose area product (DAP) (p = 0.03) and the number of implanted coils (p = 0.02) were significantly lower in direct fistulas. The median values for fluoroscopy time (FT) (p = 0.08) and number of DSA acquisitions (p = 0.84) were not significantly different between groups. There was a significantly positive correlation between DAP and FT (p = 0.003). The application of a dedicated low-dose protocol yielded a 32.6% DAP reduction. In conclusion, this study provides novel DRLs for endovascular CCF treatment using detachable coils. The data presented in this work might be used to establish new specific DRLs.